Models for Transformation: A Global Optimization Transformation method with Some Extension from Box-Cox Transformation - Wan Muhamad Amir Bin W Ahmad; Nyi Nyi Naing; Tengku Mohd Ariff Raja Hussein (STATISTIKA: Forum Teori dan Aplikasi Statistika, 2009)
The choice of a transformation has often been made in an ad hoc trial-and-error fashion but in thisresearch paper we deals with the new solution of transformation which is covering all the real numbers.The assumption of normality that gained from the optimization method is much better improvedcompared to Box-Cox transformation through the statistical P value. The biggest values of thestatistical P value (> 0.05) reflect the goodness of the normality achievement. In order to obtain theefficiency status, we will illustrate the application of transformation method with the data that aregetting from Hospital University Science Malaysia (HUSM).